The Facsimile Edition of the Nag Hammadi Codices : Codex I (Biblical Studies, Ancient Near East and Early Christianity - Book Archive pre-2000., 1977)
Contains the following tractates : The Prayer of the Apostle Paul (+ colophon); The Apocryphon of James: The Gospel of Truth; The Treatise on Resurrection; The Tripartite Tractate.